PENATALAKSANAAN FISIOTERAPI PADA KONDISI DEVELOPMENT DELAYED(DD) DENGAN METODE PLAY EXERCISE - Surya Mahendra; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Delayed  development  (DD)  is  dropping  significantly  on  the  physical,  cognitive, behavioral, emotional, or social development of a child when compared with normal children his age are caused by heredity, the child's condition, pregnancy, birth, poor nutrition, psychological, lack of motivation and stimulation that is progressive if not handle dimmediately. Problems faced in DD conditions is a decrease inpostural tone, limited functional capabilities up and running. For effective and efficien thandling, it would require the examination of growth and development with DDST examinations, examination of muscle streng thand postural tone with XOTR scale, sensory examination  and  functional  ability  with  the  GMFM.  To  address  these  problems,  the  technology used is physiotherapy interventions play a pre-play exercise exercise with standing table, sensory, tactile, and implementation neurostrukture play exercise.   Keywords : delayed development (DD), play exercise.